2012 3rd International Workshop on Emerging Trends in Software Metrics (WETSoM) 2012
DOI: 10.1109/wetsom.2012.6226992
|View full text |Cite
|
Sign up to set email alerts
|

Using early stage project data to predict change-proneness

Abstract: Several previous studies have suggested methods for predicting change-proneness based on software complexity metrics. We hypothesise that data from the early stages of a development project such as requirements and design could also be used to make such predictions. We define here a set of new metrics to capture data from the requirements and/or design stages, and derive values for these metrics using a case study project. We do find that significant differences in change-proneness can be detected between comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Some of the case studies been carried out for linking change-proneness and complexity so as to know if ay correlation exists between change-proneness and metrics. It is difficult to determine how far an individual study can be generalized, so Claire Ingram has suggested techniques (linear regression) relies on developing an accurate method for predicting change-proneness [1]. Subversion2 project from CARMEN system was used to obtain the list of code files which was representative of datasets.…”
Section: Related Workmentioning
confidence: 99%
“…Some of the case studies been carried out for linking change-proneness and complexity so as to know if ay correlation exists between change-proneness and metrics. It is difficult to determine how far an individual study can be generalized, so Claire Ingram has suggested techniques (linear regression) relies on developing an accurate method for predicting change-proneness [1]. Subversion2 project from CARMEN system was used to obtain the list of code files which was representative of datasets.…”
Section: Related Workmentioning
confidence: 99%